The influence of lower extremity kinematics on ball release velocity during in-step place kicking in rugby union - Sinclair, J.; Taylor, P. J.; Atkins, S.; Bullen, J.; Smith, A.; Hobbs, S. J. (International Journal of Performance Analysis in Sport, 2014)
Place kicking for maximal resultant ball velocity occurs many times during a rugby union game. In modern rugby union >50% of points scored come from place kicking either in the form of a conversion or a penalty. However, despite this the biomechanical mechanisms that determine kicking performance are currently unknown. This study aimed to identify aspects of in-step rugby kicking pertinent to the generation of ball velocity. Twenty male participants performed maximal velocity place kicks as lower extremity kinematics were obtained using an optoelectric motion capture system operating at 500 Hz. Multiple regression modelling was employed to identify the kinematic parameters linked to the development of ball velocity. The results show that a single kinematic measure, knee extension velocity of the kicking limb R2=0.48, p=0.01 was obtained as a significant predictor of ball-velocity. It is conceivable based on this observation, that rugby union kickers may profit from exposure to coaching and strength programmes aimed towards the alteration of kicking kinematics highlighted in the current study.